East Asian summer monsoon climates and cave hydrological cycles over Dansgaard-Oeschger events 14 to 11 revealed by a new stalagmite record from Hulu Cave. Issue 3 (November 2019) - Liang, Yijia; Wang, Yongjin; Wang, Quan; Wu, Jiangying; Shao, Qingfeng; Zhang, Zhenqiu; Yang, Shaohua; Kong, Xinggong; Edwards, R. Lawrence
Abstract: A 230 Th/U-dated stalagmite from Hulu Cave was analyzed for δ 18 O, δ 13 C, and trace elements. A 10-yr-resolution δ 18 O record, spanning 51.7–42.6 ka, revealed Dansgaard-Oeschger (DO) events 14 to 11. A similar rapid transition and synchronous timing of the onset of DO 12 is evident between the Greenland and Hulu Cave records, which suggests a common forcing mechanism of DO cycles in the North Atlantic and monsoonal region of Asia. Centennial-scale monsoonal oscillations in the cave δ 18 O record are indicative of hydroclimatic instability during interstadials. After removing the signals of remote moisture sources, the proportion of moisture from nearby sources is found to be higher during stadials than during interstadials. To explain this, we propose that the movement of the westerly jet is an important control on the balance of nearby and distant moisture sources in East Asia. In addition, the records of δ 13 C and trace element ratios, which are proxies of local environmental changes, resemble the δ 18 O record on the scale of DO cycles, as well as on even shorter timescales. This suggests that hydrological processes and biological activity at the cave site respond sensitively to the monsoonal changes.